Essential communications skills for managers. - St. John, Walter (Corporate communication collection., 2017)
The purpose of this book is to provide practicing and aspiring managers and students of management a practical and comprehensive reference source for communicating on the job with all people in all situations. This "how-to" book provides readers with the essential knowledge, attitudes, and skills to perform the communicating aspects of their routine and special duties. The information is presented in two volumes. Each topic is divided into "Things to Know" and "Things to Do."